(untitled) (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2022)
This study aims to determine the effect of group counseling services to improve students’ low self-esteem in high school. The research was conducted on students of class XI SMA Negeri 1 Binjai. This type of research is quantitative research with an experimental approach. The data collection instrument was a closed questionnaire. The sampling technique was done by purposive sampling. The research sample is class XI-1 students with a total of 30 people. Based on the results of the paired sample t test, there was a significant difference between the results before and after being given group counseling services. Based on the results of the analysis of the paired sample t test, the results obtained are tcount > ttable, namely 9.334 > 1.69726 and the value of sig (2-tailed) 0.000 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is an effect on students’ low self-esteem before being given group counseling services and after being given group counseling services to class XI students of SMA Negeri 1 Binjai.